LEADERSHIP STYLES AND PERSONALITY VARIABLES: THEIR EFFECT ON SCHOOL PERFORMANCE - Hurst, Brian Evan (Acta Scientiae et Intellectus, 2024)
The purpose of this literature review, is to investigate the relationship between an educational leaders’ personality type and leadership style and their effect on school performance. Although leadership has been dissected and compared with personality in past literature, a scant amount of study (and information) has been conducted or is available, to support the theory of combinations of leadership styles and personality types. Multiple and current studies, have compartmentalized leadership style to transformational or transactional styles with the occasional obvious “no-fit” style to the previous to conduct relational research. Leadership is not relegated to only two styles. Styles change. Personality types, on the other hand, change in rare circumstances. Few studies have examined the variables of leadership style and personality types in current research. This literature review has the potential to lessen this gap by empirically studying these possible relationships. Implications and findings of this review could possibly identify links within existing leadership-personality literature as well as be helpful in guiding the development of future leaders at the instructional level.